2010
DOI: 10.4111/kju.2010.51.1.40
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Study of the Effects of the Tension-Free Vaginal Tape Procedure for Female Stress Urinary Incontinence on Voiding, Storage, and Patient Satisfaction: A Post-Hoc Analysis

Abstract: PurposeWe assessed the long-term effects of the tension-free vaginal tape (TVT) procedure for stress urinary incontinence (SUI) on voiding, storage, and patient satisfaction.Materials and MethodsThis retrospective study examined the records of 134 patients who had undergone the TVT procedure for SUI and were followed up for more than 5 years. Voiding function was evaluated by measuring maximum urinary flow rate (MFR), post-void residual urine volume (PVR), and storage function by using a voiding diary. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Among the parameters analyzed by these authors were the bladder volumes determined one month, one year, and five years after the procedure. The authors did not document significant changes in the bladder volume of patients subjected to TVT surgery [31]. Our findings seem to be consistent with this observation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among the parameters analyzed by these authors were the bladder volumes determined one month, one year, and five years after the procedure. The authors did not document significant changes in the bladder volume of patients subjected to TVT surgery [31]. Our findings seem to be consistent with this observation.…”
Section: Discussionsupporting
confidence: 91%
“…Instead, they only showed that the bladder volume of patients subjected to Burch procedure decreased significantly, contrary to persons who were operated on according to TVT protocol [30]. The treatment outcomes in patients with stress urinary incontinence were also studied by Han et al [31]. Among the parameters analyzed by these authors were the bladder volumes determined one month, one year, and five years after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Voiding dysfunction had a significant negative impact on subjective patient satisfaction; the weaker the maximum flow rate, the less was patient satisfaction . Postoperative voiding dysfunction improved with time in most patients with mild voiding symptoms, but this was less likely to happen when voiding dysfunction was severe . None of the patients who underwent the retropubic approach needed ancillary continent procedures, but 2.3% of them needed sling release secondary to severe voiding dysfunction.…”
Section: Discussionmentioning
confidence: 99%